Blended and Innovative Teaching Strategies for a Third Year Process Instrumentation and Control Unit: An Effective Course Delivery - Sen, Tushar (Infonomics Society, 2014)
Blended learning is a student centered flexible, self-paced multi model approach to learning. The blended mode of learning has become increasingly popular in higher education. However, blended teaching requires careful scheduling to balance face-to-face and online components of the classes and also quality of blended teaching depend on teacher’s ability to design and deliver the courses. Therefore, in this paper the various thoughtful design competencies has been applied on an undergraduate 3rd year large core unit, “Process instrumentation and control-328” at Curtin University, Perth WA for effective unit delivery. These competencies such as implementation of alternative group project based assessment, simulation based e-learning, problem based teaching, integration with real world as ‘active learning’ competency and digital full course materials, online work load, discussion, presentation, feedback to student as ‘active teaching & technological’ competency and finally administrative / leadership competency such as grading visible for students, application of blackboard, students behavior etc. were applied in effective course delivery. Students opinions (eVALUate results) reflects the use of a thoughtful designing of a blended teaching approach made by their lecturer in the year of 2010 in terms of well-designed units rich with resources, workload, timely feedback, visible grading, good interaction, quality of teaching, assessment tasks, motivation and high satisfaction as very high ‘positive learning experience’ which exceeds the target of University and faculty agreement. Survey results also revealed that integration with real world by industry visit was an important part of student’s overall learning on process instrumentation and control unit 328.